Sleep and hippocampus: do we search for the right things? - Brankačk, Jurij; Platt, Bettina; Riedel, Gernot (Progress in neuro-psychopharmacology & biological psychiatry, 2009)
In addition to its established function in brain restoration, energy saving, circadian homeostasis, thermoregulation, and ontogenetic brain development, sleep is involved in replay and restructuring of memory representations that may lead to memory consolidation. The degree of availability of these memory-related functions in various species, and in disparate environmental and behavioral situations is widely debated. Generally it seems that species which can afford to sleep deeply show an involvement of sleep in learning and memory, both, hippocampus-dependent and hippocampus-independent. Inconsistencies in the sleep literature concerning the importance of certain sleep states for learning of various tasks and the involvement of different types of memory do not disprove that sleep plays a role in memory consolidation. In this review, we attempt to reconcile some of the seemingly antagonistic theories of sleep function in a succinct and unbiased manner and develop an eclectic view of its role in learning and memory.